The role of paleolimnology in climate and environment reconstruction and lake restoration in light of research on selected bioindicators - Wojewódka, Marta (Array, 2020)
Paleolimnologists and ecologists study biotic and abiotic variables to track long-term and short-term environment changes. Microscopic invertebrates, phytoplankton of freshwater ecosystems, and pollen grains have been extensively studied during the last decades. Surveys of modern and fossil biota composition might provide information about past changes caused by climate alteration and human activity. Furthermore, research on the modern population of these biological proxies may be utilized to assess environmental quality and restoration measures. This paper synthesizes knowledge of the use of selected microscopic invertebrates (Cladocera, Copepoda, Ostracoda, Rotifera), phytoplankton, and pollen grains for the aforementioned issues. This review shows that the ability of these biological proxies to indicate environment changes is versatile. Some of them may be utilized to track long-term changes of temperature (pollen) or pH (Diatomeae). Others are useful to reconstruct paleosalinity (Ostracoda) or conductivity (Ostracoda, Diatomeae), while the utilization of Rotifera and Copepoda in paleoreconstruction, due to the very poor preservation of the remains, is very limited, although these fauna are very useful for assessing modern water quality.